Electric brain signals foundations and applications of biophysical modeling - Halnes, Geir 1976- (Cambridge University Press, 2024)
It is common to study the electric activity of neurons by measuring the electric potential in the extracellular space of the brain. However, interpreting such measurements requires knowledge of the biophysics underlying the electric signals. Written by leading experts in the field, this volume presents the biophysical foundations of the signals as well as results from long-term research into biophysics-based forward-modeling of extracellular brain signals. This includes applications using the open-source simulation tool LFPy, developed and provided by the authors. Starting with the physical theory of electricity in the brain, this book explains how this theory is used to simulate neuronal activity and the resulting extracellular potentials. Example applications of the theory to model representations of real neural systems are included throughout, making this an invaluable resource for students and scientists who wish to understand the brain through analysis of electric brain signals, using biophysics-based modeling.